The Influence of Information Literacy, Technology, And Communication on Improving Digital Competence of Students of STMIK Mardira Indonesia, Bandung City - Rajuman S, Rajuman S; Syaodih, Erliany; Kusnadi, Dadang (Journal of Economics, Management, and Entrepreneurship, 2024)
This study examines the impact of information, technology, and communication literacy on enhancing students' digital competence at STMIK Mardira Indonesia, Bandung City. Rapid technological advancements have transformed numerous facets of life, necessitating the education sector to adapt to enhance the quality of human resources for competition in the digital age. Digital competence is a crucial ability for students navigating the progressively technology-driven workforce. This competency encompasses critical, creative, and ethical comprehension of technology utilization and the capacity to manage information efficiently. Information literacy aids individuals in identifying information requirements, locating, assessing, and utilizing information judiciously. Simultaneously, technology and communication promote digital competencies by granting access to diverse resources and enhancing the capacity to disseminate knowledge efficiently. This study employs a quantitative methodology utilizing a saturation sampling technique, wherein the complete population of 46 individuals served as the research sample. Data analysis was conducted employing multiple regression procedures, utilizing validity, reliability, and hypothesis testing as statistical analytic tools. The study indicated that technology and communication significantly enhance pupils' digital competency. Students with proficient access to technology and strong communication skills are more capable of enhancing their digital competence. Nonetheless, the study's findings indicated that information literacy did not significantly enhance students' digital competence. This study indicates that while information literacy is a crucial component of higher education, technological and communicative aspects are more influential in developing students' digital competence in the contemporary digital landscape. Consequently, universities must prioritize enhancing technology and communication competencies within the curriculum and educational programs to better prepare students for the digital workforce. Despite the lack of noteworthy findings regarding information literacy in this study, educational institutions must continue to promote awareness of their value as a component of 21st-century abilities. The findings of this study are anticipated to serve as a reference for policymakers in formulating more effective ways to enhance students' digital competency, hence augmenting the competitiveness of graduates in the progressively competitive landscape of globalization.